Autobiographical Memory and Social Identity in Autism: Preliminary Results of Social Positioning and Cognitive Intervention - Wantzen, Prany; Boursette, Amélie; Zante, Elodie; Mioche, Jeanne; Eustache, Francis; Guénolé, Fabian; Baleyte, Jean-Marc; Guillery-Girard, Bérengère (Frontiers in Psychology, 2021)
Autobiographical memory (AM) is intimately linked to the self-concept and presents directive, identity, social, and adaptive functions. It is now accepted that individuals with autism spectrum disorders (ASD) show an atypical AM, which may be closely associated with social communication deficits. This may result in qualitatively different autobiographical narratives affecting notably social identity. The present study aimed to investigate this concept and to develop a cognitive intervention dedicated to ASD individuals. First, 13 adolescents with ASD and 13 controls were provided an AM interview with an original quotation devoted to analyzing social self. We observed that the ASD narratives focused on the family to the detriment of references to extended social spheres, compared to controls. Besides, ASD participants do not include themselves in the social group in their narratives and produce more references to others compared to typically developing participants. Second, we have elaborated a cognitive intervention program targeting AM and consisting of individual and group sessions. We conducted pilots with three adolescents with ASD aged 12, 16, and 17 years old. The preliminary results showed that the program increased extra-family narrative references for the two youngest adolescents with more social integration markers. Our studies provide interesting social positioning findings in autobiographical narratives in ASD and how AM as a vector of social interaction can be reinvested in a therapeutic proposal.